Identification, Characterization, and Transcriptional Reprogramming of Epithelial Stem Cells and Intestinal Enteroids in Simian Immunodeficiency Virus Infected Rhesus Macaques - Boby, Nongthombam; Cao, Xuewei; Ransom, Alyssa; Pace, Barcley T.; Mabee, Christopher; Shroyer, Monica N.; Das, Arpita; Didier, Peter J.; Srivastav, Sudesh K.; Porter, Edith; Sha, Qiuying; Pahar, Bapi (Frontiers in Immunology, 2021)
Epithelial cell injury and impaired epithelial regeneration are considered key features in HIV pathogenesis and contribute to HIV-induced generalized immune activation. Understanding the molecular mechanisms underlying the disrupted epithelial regeneration might provide an alternative approach for the treatment of HIV-mediated enteropathy and immune activation. We have observed a significant increased presence of alpha defensin5+ (HD5) Paneth cells and proliferating Ki67+ epithelial cells as well as decreased expression of E-cadherin expression in epithelial cells during SIV infection. SIV infection did not significantly influence the frequency of LGR5+ stem cells, but the frequency of HD5+ cells was significantly higher compared to uninfected controls in jejunum. Our global transcriptomics analysis of enteroids provided novel information about highly significant changes in several important pathways like metabolic, TCA cycle, and oxidative phosphorylation, where the majority of the differentially expressed genes were downregulated in enteroids grown from chronically SIV-infected macaques compared to the SIV-uninfected controls. Despite the lack of significant reduction in LGR5+ stem cell population, the dysregulation of several intestinal stem cell niche factors including Notch, mTOR, AMPK and Wnt pathways as well as persistence of inflammatory cytokines and chemokines and loss of epithelial barrier function in enteroids further supports that SIV infection impacts on epithelial cell proliferation and intestinal homeostasis.